INCIDENCE OF SECONDARY ROOT CARIES LESIONS IN PATIENTS REFERRED FOR TREATMENT IN THE FACULTY OF DENTAL MEDICINE - SOFIA. - Mirela Marinova-Takorova (Peytchinski Publishing, 2014)
Purpose: The aim of the presented study was to determine the incidence of secondary root caries lesions in patients referred for treatment in the Faculty of Dental Medicine - Sofia. Material/Methods: The subjects who took part in the study were patients referred for treatment of caries lesions in the Faculty of Dental Medicine, Sofia. They were interviewed for smoking, presence of systematic diseases and medications and debris and plaque were removed from natural teeth prior to examination. Dental examination was carried out with a dental mirror and a probe. Decayed, missed and filled teeth (DMFT) were recorded. Root caries lesions, restorations of those lesions and secondary caries lesions were recorded separately. Results: A total number of 603 patients were examined. The frequency of appearance of root caries in the investigated population was 33.5% (202 patients). The whole number of root caries lesions was 857. Three hundred forty three (41.4%) of those lesions were restored. Presence of secondary caries lesions was observed in 138 cases (39.1%). Conclusions: Based on the data obtained from the presented study it may be concluded that most of the root caries lesions remain untreated (58.8%). Secondary carious was diagnosed in 39.1% of the root caries restorations. The patients with secondary caries lesions presented with higher incidence of concomitant diseases and lower incidence of smoking.